PENGARUH KONTEN YOUTUBE VLOGGER "YOSHIOLO" TERHADAP PERILAKU KONSUMTIF MAHASISWA UTM - M Chairul Aminullah (Journal of Student Research, 2023)
Abstract. Social media is a platform that is very open, which allows anyone to produce and consume it. This makes social media dominate internet content as the most frequently accessed by the Indonesian people. One of the social media that has an influence on society today, especially for social media that is able to visually display content that is easy to understand compared to the type of online media that just displays photos or even just a written message. Youtube is a solution used by some people in the world in determining and finding the desire they are looking for. From social media, this very open platform allows anyone to produce and consume it. This makes social media dominate internet content as the most frequently accessed by the Indonesian people. YouTube is also one of the many social media platforms that is widely used to share free information and display content in the form of videos. YouTube contains a wide range of topics, and everyone can post videos on this platform, which is why it is so popular. 272.1 million people live in Indonesia, 64% of the country’s population has an internet connection. With 88% of the population using YouTube, it is the most popular social media platform in Indonesia and the second most popular platform is occupied by WhatsApp with 84% of users. Users can display and distribute content on YouTube in addition to using it as a source of information. Using a YouTube account is very cheap and easy compared to using traditional media, which entails a lot of money. YouTube is growing in popularity not only because it is cheaper but also because anyone can post a video for a wide audience to watch. Because of how convenient it is to use YouTube, because viewers can not only see the content, but they can respond in the comments section. However, through this convenience one can potentially follow what his idols are doing on this platform. Just like a Youtuber who is able to provide social effects on the audience like "YOSHIOLO" who explains his content about lifestyle goods whose segment called "How Much Does Your Outfit Cost?" is currently favored by Gen Z specifically for students. The presence of this content increases the desire of young people, especially students, to use these lifestyle items to boost appearance and even for appreciation events in the campus environment. Through this incident, it causes consumptive attitudes towards the younger generation who are lacking in managing finances because they are entangled in the beautiful world of Fashion Style shown in this Youtube content. The need for understanding and awareness in seeing impressions for them, especially students, in preventing this phenomenon through social media. Keywords: Social Media, YouTube, Consumptive.